2008
DOI: 10.1111/j.1574-6968.2008.01343.x
|View full text |Cite
|
Sign up to set email alerts
|

Linkage of microbial ecology to phenotype: correlation of rumen microbial ecology to cattle's feed efficiency

Abstract: Linkage of rumen microbial structure to host phenotypical traits may enhance the understanding of host-microbial interactions in livestock species. This study used culture-independent PCR-denaturing gradient gel electrophoresis (PCR-DGGE) to investigate the microbial profiles in the rumen of cattle differing in feed efficiency. The analysis of detectable bacterial PCR-DGGE profiles showed that the profiles generated from efficient steers clustered together and were clearly separated from those obtained from in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
203
6
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 253 publications
(223 citation statements)
references
References 22 publications
11
203
6
3
Order By: Relevance
“…Such effects are supported by numerous studies that have shown different animal species, even those that are closely related, possess host-specific microbiomes [41,42,83,[121][122][123] and by the finding that strains of a single microbial species that are isolated from different host species are genetically distinct and more adept for survival in their host of origin [10]. Diet is of critical importance to many, if not all microbiomes.…”
Section: Host Influences-the Tertiary Evolutionary Pressuresmentioning
confidence: 54%
“…Such effects are supported by numerous studies that have shown different animal species, even those that are closely related, possess host-specific microbiomes [41,42,83,[121][122][123] and by the finding that strains of a single microbial species that are isolated from different host species are genetically distinct and more adept for survival in their host of origin [10]. Diet is of critical importance to many, if not all microbiomes.…”
Section: Host Influences-the Tertiary Evolutionary Pressuresmentioning
confidence: 54%
“…Low-RFI animals (Nkrumah et al 2006;Hegarty et al 2007). Comparisons of ruminal microbiomes between low-and high-RFI animals using a variety of methods have shown differences in bacterial and archaeal community profiles correlated with RFI, although these associations are often influenced by the energy content of the diet (Guan et al 2008;Zhou et al 2010;Carberry et al 2012;Hernandez-Sanabria et al 2012). Methanogen-related differences observed in these studies included a specific high-RFI-related PCR-DGGE band associated with Methanobrevibacter smithii PS (Zhou et al 2010), an elevated abundance of Methanosphaera stadtmanae, and Methanobrevibacter sp.…”
Section: Discussionmentioning
confidence: 99%
“…These methods using a non-targeted approach are able to pick up differences and similarities in the community of different microbial groups in the rumen associated with host ruminant species, diet and feed efficiency (Larue et al, 2005;Sadet et al, 2007;Guan et al, 2008 and references above; Suen et al, 2011) but they do not provide direct sequence information. In addition, the number of bands or peaks detected by these techniques is several orders of magnitude lower than the estimated diversity in the rumen (Hess et al, 2011;Kim et al, 2011).…”
Section: Rumen Microbial Diversitymentioning
confidence: 99%